2010
DOI: 10.1111/j.1600-0625.2010.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

E6 and E7 proteins from different beta-papillomaviruses types do not interfere in UVB-induced apoptosis of HaCaT keratinocytes

Abstract: :  Beta‐papillomaviruses (beta‐HPV) have been linked to the development of skin cancer in humans. Because both E6 and E7 proteins from beta‐HPV have been involved in the potential carcinogenicity of these viruses, we investigated their role on UVB‐induced apoptosis in HaCaT cell line. HaCaT cells have been transduced with both E6/E7 using a retroviral system and treated with PRIMA‐1. Apoptosis was assessed by flow cytometry to measure mitochondrial membrane potential and DNA fragmentation. HaCat keratinocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
3
10
1
Order By: Relevance
“…A number of recent studies show that UVB light induces apoptosis in keratinocytes [24,25,26]. In keeping with this observation, intact nuclei were observed in control, and cells treated only with BHE, whereas significant nuclear fragmentation (characteristic of apoptotic body formation) was observed in UVB-irradiated cells (apoptotic index, 19.3).…”
Section: Resultssupporting
confidence: 68%
“…A number of recent studies show that UVB light induces apoptosis in keratinocytes [24,25,26]. In keeping with this observation, intact nuclei were observed in control, and cells treated only with BHE, whereas significant nuclear fragmentation (characteristic of apoptotic body formation) was observed in UVB-irradiated cells (apoptotic index, 19.3).…”
Section: Resultssupporting
confidence: 68%
“…However, E6 gene expression from several cutaneous HPV types protects keratinocytes from UV-B-induced apoptosis (50,51) by mediating the degradation or reduction of the levels of the proapoptotic Bak protein, thereby preventing the release of proapoptotic factors from the mitochondria (52,53). However, this finding was not confirmed when E6/E7 was expressed in HaCat keratinocytes (54). It has been demonstrated that wt p53 induces the downregulation of E6 from HPV5, HPV20, and HPV38 (55), supporting the notion of a role for E6 in oncogenesis.…”
Section: Discussioncontrasting
confidence: 43%
“…HaCat keratinocytes transduced with both E6 and E7 genes of beta-HPV types do not demonstrate any inhibition of UVB-induced apoptosis (26). In our study, repression of E6/E7 expression concomitantly reduced the IL-6 and IL-8 expressions and cell proliferation.…”
Section: Discussionmentioning
confidence: 49%